Respuesta :
Answer:
First Term: [tex]a_{1} = -9[/tex]
Common Difference : d= 4
Recursive formula:[tex]a_{n} = -9 + 4(n-1)[/tex]
Step-by-step explanation:
Here we are going to use the arithmetic progression formula:
[tex]a_{n} = a_{1} + (n-1) d[/tex]
[tex]a_{n} : nth - term[/tex]
d :common difference
Since we are given the 5th term and 19th term, we can write them as :
[tex]a_{5} = a_{1} + (5-1) d[/tex]
[tex]a_{5} = a_{1} + (4) d[/tex]
as [tex]a_{5}=7[/tex]
so,
[tex] 7 = a_{1} + (4) d[/tex] -------------------(Equation 1)
Moreover, using same formula for 19th term
[tex]a_{19} = a_{1} + (19-1) d[/tex]
[tex]a_{19} = a_{1} + (18) d[/tex]
As [tex]a_{19} = 63[/tex]
So,
[tex]63=a_{1} + (18) d[/tex] --------------------(Equation 2)
From Equation 1, we have:
[tex]a_{1} = 7-4d[/tex]
put the value in equation 2:
[tex]63= 7-4d+18d [/tex]
[tex]63=7+14d[/tex]
[tex]63-7 = 14d\\14d = 56\\d= \frac{56}{14} \\d=4[/tex]
Which is the common difference
Now put the value of d in equation 1:
[tex]7= a_{1} +4 (4)\\7=a_{1} +16\\7-16 = a_{1} \\[/tex]
[tex]a_{1} = -9[/tex]
Which is the first term
Putting the firm term and common difference in the initial arithmetic progression formula:
[tex]a_{n} = a_{1} + (n-1) d[/tex]
[tex]a_{n}= -9 + (n-1)d \\[/tex]
[tex]a_{n}= -9 + 4(n-1)[/tex]
Which is the recursive formula of the sequence